Kedudukan Hukum Janda dalam Perjanjian Baru berdasarkan Tiga Aspek: Anak, Harta Warisan, dan Relasi dengan Allah - Saefatu, Meyrlin (Institut Agama Kristen Negeri Kupang, 2025)
In the New Testament, we can find various texts that speak about widows, especially in the Synoptic Gospels, the Acts of the Apostles, and Paul's Letters. Generally speaking, widows were regarded as a disadvantaged or underprivileged social group in Jewish society. Widows often faced negative stigma, particularly those who did not have children or an inheritance from their deceased husbands. The purpose of this writing is to gain an understanding of the legal status of widows in Jewish society during the New Testament period, particularly according to the authors Luke and Paul, especially in 1 Timothy. To achieve this, the writer will study and analyze various texts or literature (textual analysis), especially the Gospel of Luke and Paul's Letters to Timothy, which discuss the legal status of widows, including literature from the Rabbinic tradition. Based on this study, it becomes evident that the status of widows in Jewish society during the New Testament period was not always negative. The status of being a widow was also viewed positively, with legal guarantees and protections. These guarantees were influenced by three important aspects: children, inheritance, and the widow's relationship with God. These aspects significantly determined the status of widows in Jewish society during the New Testament period.